Analisis Penggunaan Narkotika dengan Alasan Kesehatan dalam Perspektif Hukum Pidana Islam dan Undang-Undang No 35 Tahun 2009 Tentang Narkotika - Nasiri, Nasiri; Isa, Abdullah (Taruna Law: Journal of Law and Syariah, 2023)
In Islamic teachings, there are five main objectives of Islamic law that appear. One of the five goals is maintenance of the mind. Therefore, in order to maintain the purity of the mind, it is forbidden to consume food or drink that damages the health of the human mind. Like narcotics, methamphetamine, and all kinds of other illegal drugs. However, this law does not apply to people who are sick and can only recover by consuming the drug. In other words, illegal drugs may be consumed when needed in order to achieve one's health. One of the uses of Narcotics for health reasons in Indonesia is legalized as contained in the law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, especially in article 7. Treatment is a step that is always related to society, where people always need treatment. Drugs containing narcotics are drugs that require special supervision from the pharmacy and are supervised by the government so that their use and circulation are not misused. The definition of narcotics is a substance or drug derived from a plant, both synthetic and semi-synthetic, which can cause a decrease or change in consciousness, relieve pain, and even cause dependence on the user. However, it is different for medical needs, narcotics can still be used. However, the use of narcotics in Indonesia must refer to the rules set by the Ministry of Health.